Focus on Indonesia: Reconstructing Cultural Contents in English Language Teaching Materials - Berli Arta (The Future of Education Journal, 2022)
It is undeniable that language and culture are formed and shaped in the way they influence each other. This fact is really important to understand how cultural contents play their roles in English Language Teaching and Learning. Currently, there have been more diverse contested cultural contents in language learning, especially in Indonesian contexts as cultural understanding of English-speaking countries, local norms, and other countries can be opposite each other. However, to optimize learning outcome, those cultures above should be equally understood to enable language learners can fully understand how the language is used in particular contexts. This complex discussion about the cultural contents is presented in this article along with prominent arguments of reconstructing the learning contents by considering three main aspects in which English is constructed in English-speaking countries, taught in Indonesia, and used as medium of communication in South East Asia.